Ecologia de saberes e práticas na produção de saúde no assentamento da antiga fazenda Annoni, no município de Pontão/RS - Germani, Alessandra Regina Müller (2018)
Considering that the struggle for land and Agrarian Reform are not isolated struggles and that other struggles are unfolding from it, as is the case of health; and that the struggle for land and Agrarian Reform unleashed on the Annoni Farm can be considered as a fertile ground for learning and fostering new health experiences; and understanding the importance of breaking with the invisibility, to emerge / "sprout" these experiences, is that this study had as a general object to analyze the experience of fight for health developed in the settlement of the former Fazenda Annoni, located in the municipality of Pontão / RS , in order to identify how the relationships between scientific and popular knowledge and practices have been constructed in the production of health actions in the settlement. For that, a case-study research was developed with a qualitative approach. The methodological procedures adopted included an exploratory, bibliographic, documentary and field research, developed in an interrelated way. For the analysis and interpretation of the data, we used the Data Triangulation and the Content Analysis Method, from which the following categories emerged: Historical antecedents to the occupation of Fazenda Annoni - a rescue on experiences of struggle for land and Agrarian Reform in northern region of Rio Grande do Sul / RS; From occupation to camp - the experience of fighting for health that emerges / "springs" from the struggle for land represents the fight against disease and in defense of the lives of families; From provisional to definitive settlement - the experience of fighting for health that emerges / "springs" from the struggle for land represents the reorganization and strengthening of the solidarity network and cooperation in the production of health actions directed at families, and finally; The establishment from the formation of the municipality of Pontão / RS - the experience of struggle for health represents ally efforts for the construction of the official health system - SUS. In conclusion, it is understood that the relations between scientific and popular knowledge and practices, identified in the experience of struggle for health built in the context of the struggle and conquest of the land, can be considered as an alternative movement for the production of health actions, because they are aligned with the principles that underpin the movement for the struggle for land, Agrarian Reform and the right to health and in defense of the SUS, and thus promoting an Ecology of knowledge. From the emancipation of the municipality, the settlement already constituted is allied to the process of construction of the official health system - SUS. However, there are experiences of tensions in which scientific knowledge in health tends to dominate the other knowledge present in the community, generating movements and mobilizations in the settlement with a view to confronting this way of thinking and doing in health, seeking with this the promotion of an Ecology of knowledge.